Pengaruh Pengetahuan Halal dan Brand Awareness terhadap Keputusan Pembelian Produk Mixue di Aplikasi Gofood pada Mahasiswa Fakultas Pertanian Universitas Muhammadiyah Sumatera Utara - Silvia Berta Lia Sianipar; Haryaji Catur Putera Hasman; Finta Aramita (Universitas Muhammadiyah Surabaya, 2023)
This research aims to know and analyze the influence of Halal Knowledge and Brand Awareness on the Purchasing Decision of Mixue Products in GoFood Application on students of Faculty of Agriculture, University of Muhammadiyah North Sumatra. This type of research is quantitative research with the type of data used being primary data and secondary data obtained from questionnaires. The population in this study was all students and students of the Faculty of Agriculture of the University of Muhammadiyah University of North Sumatra starting from 2019 to 2021 who are still actively studying at the University of Muhammadiyah North Sumatra who have shopped at least twice on the GoFood application. The sample in the study was 98 people. The sampling method uses nonprobability sampling methods with purposive sampling techniques and the data analysis method used is descriptive statistical analysis. The results showed that Halal Knowledge has a positive and significant effect on purchasing decisions. This is evidenced by the calculated t value of 2,799 > t table of 1,985, Brand Awareness has a positive and significant effect on purchasing decisions. This is evidenced by the t value of 2,916 > t table of 1,985, and there is a positive and significant bearing between the influence of Halal Knowledge and Brand Awareness on Purchasing Decisions. This is evidenced through the calculating F value of 8.628 > F table of 2.36.